Managerial Talent, Motivation, and Self-Selection into Public Management - Josse Delfgaauw; Robert Dur (Tinbergen Institute, 2008)
The quality of public management is a recurrent concern in many countries. Calls to attract the economy's best and brightest managers to the public sector abound. This paper studies self-selection into managerial and non-managerial positions in the public and private sector, using a model of a perfectly competitive economy where people differ in managerial ability and in public service motivation. We find that, if demand for public sector output is not too high, the equilibrium return to managerial ability is always highest in the private sector. As a result, relatively many of the more able managers self-select into the private sector. Since this outcome is efficient, our analysis implies that attracting a more able managerial workforce to the public sector by increasing remuneration to private-sector levels is not cost-efficient.
Keywords: H83; J24; J3; J45; 330; Public Management; Public Service Motivation; Managerial Ability; Self-Selection; Führungskräfte; Qualifikation; Leistungsmotivation; Arbeitsmobilität; Öffentlicher Sektor; Vergleich; Privatwirtschaft; Vollkommener Wettbewerb; Theorie